Cellulose Acetate and Supercritical Carbon Dioxide: Membranes, Nanoparticles, Microparticles and Nanostructured Filaments - Stefano Cardea (Polymers, 2020)
Cellulose acetate (CA) is a very versatile biocompatible polymer used in various industrial sectors. Therefore, depending on the application, different morphologies are required. Different processes at industrial scale are commonly employed to obtain CA micro or nanoparticles (discontinuous structures) or CA membranes (continuous structures with discontinuities). In this work, two supercritical carbon dioxide (scCO2) based techniques, such as the semi-continuous supercritical antisolvent process (SAS) and the supercritical fluid phase inversion process, in which scCO2 plays the role of antisolvent, were employed. Varying the kind of organic solvent used to prepare the polymeric solution, the polymer concentration, and operating pressure and temperature, it was possible to tune the characteristics of the obtained material. In particular, using acetone as the organic solvent, filaments constituted by nanoparticles, expanded microparticles, nanoparticles with a mean diameter lower than 80 nm, and microporous membranes were obtained, varying the operating conditions. The attainment of spherical micron-sized particles was instead achieved using a mixture of acetone and DMSO as the organic solvent. Therefore, the versatility of the supercritical carbon dioxide-based techniques has been confirmed, and it was possible to obtain, using a single experimental plant, various morphologies of cellulose acetate (with controllable particles’ or pores’ diameters) by varying the operating conditions.